QARAQALPAQ XALQÍNÍŃ HÁREKTLI OYÍNLARÍN ÓTKERIWDE ÓZINE SAY ÓZGEShELIKLERI - Shılmanov, R. (SCIENCE and SOCIETY, 2023)
This article provides information about the division of national outdoor games into varieties, the interaction of playfulness, and the characteristics of the outdoor games themselves. The necessary information can be obtained by young physical education teachers, doctoral students, masters, bachelors.